Health Psychology Bulletin: Improving Publication Practices to Accelerate Scientific Progress - Gjalt-Jorn Ygram Peters (Health Psychology Bulletin, 2017)
The instrument of scientific publishing, originally a necessary tool to enable development of a global science, has evolved relatively little in response to technological advances. Current scientific publishing practices incentivize a number of harmful approaches to research. Health Psychology Bulletin was founded to address these issues. Health Psychology Bulletin (HPB) is a new open access journal that actively promotes full disclosure through publication of replication and analysis packages and that explicitly welcomes null findings, reports of failed manipulation, replications, as well as regular contributions. HPB strives to publish all conducted studies in a manner that maximizes the potential lessons that can be learned, fostering a shift from a competitive to a collaborative model of science. HPB also implements a double blind peer reviewing procedure that is unblinded and citable once an article is accepted, and HPB will strive to enable post-publication peer reviews. Finally, HPB offers authors the possibility to submit (and publish) their introductions, methods, study protocols and replication packages before data collection, thereby benefiting from the peer review process in optimization of their methodologies. By implementing these innovations, HPB aims to contribute to remedying a number of problems that have recently been identified in the way health psychology science is conducted. In addition, the European Health Psychology Society aims to offer a new accessible, affordable, and flexible outlet to her members (and non-member health psychology researchers).